Focal radiation necrosis of the brain in patients with melanoma brain metastases treated with pembrolizumab. (21st August 2018) - Du Four, Stephanie; Janssen, Yanina; Michotte, Alex; Van Binst, Anne‐Marie; Van den Begin, Robbe; Duerinck, Johnny; Neyns, Bart
Abstract: Introduction: Up to 60% of patients with metastatic melanoma develop melanoma brain metastasis (MBM) during the course of their disease. Surgery, radiosurgery (SRS), stereotactic radiotherapy (SRT), and whole‐brain radiation therapy (WBRT) or combinations of these are commonly used local treatment modalities. Inhibitory monoclonal antibodies against the CTLA‐4 and PD‐1 immune checkpoint receptors significantly improved the survival of metastatic melanoma patients, including patients with MBM. This prolonged survival, and potentially also the immunostimulatory mechanisms, may expose patients to a higher risk for long‐term complications such as focal postradiation necrosis of the brain (RNB). Methods: We analyzed the incidence of pseudotumoral RNB in a single institution cohort of 142 melanoma patients that were prospectively followed after starting treatment with pembrolizumab in an expanded access program. Results: Of the 142 patients, 43 (30.7%) patients had MBM at initiation pembrolizumab. Of these, 31 (72.1%) were treated with SRS, 8 (18.6%) with WBRT while 4 (9.3%) had no prior local therapy. Of patients treated with RT, 28 (71.1%) received RT before the initiation of pembrolizumab. 5 (12.8%) patients developed a new symptomatic pseudotumoral lesion at a median time of 11.15 months (range 8‐46) after the RT. In all patients, the diagnosis of RNB was radiologically confirmed. The RNB was treated with corticosteroids in two patients, bevacizumab in two patients, and surgery in three symptomatic patients. The diagnosis was histologically confirmed in the patients treated with surgery. Conclusion: Melanoma patients with MBM treated with radiosurgery and showing a beneficial response to pembrolizumab are at risk for late RNB. In case of suspected isolated progression at the site of a previously irradiated MBM, the diagnosis of RNB should be considered. Abstract : Due to the advances in immunotherapeutic treatments, patients with metastatic melanoma have an increased survival. In these patients, melanoma brain metastases are often treated with radiotherapy. Due to the increased overall survival, the patients are more prone to the development of long‐term complications such as radiation necrosis. We report specifically report the incidence of focal pseudotumoral radiation necrosis of the brain in a patient population treated with the anti‐PD‐1 monoclonal antibody pembrolizumab.